Production of paper from non-wood: a review - Mahazir, Nur Sakinah; Othman, Siti Amira (2021)
Wood have been main of raw material for paper production around world. This lead to negative effect for our forest and environment. Aim of this paper is to review other suitable non-wood to replace wood as main material for paper production. Main material in this review are banana fiber and pineapple leaves.